The reliability of an intermittent sprint cycling protocol on a Wattbike Pro in hot conditions - Ross, C.; Clarke, N.; Oxford, S.; Morris, M. G.; Thake, C. D. (Journal of Science and Cycling, 2023)
The reliability of sport science tools are important where meaningful change is assessed. However, there is little research identifying the reliability of an intermittent high intensity protocol in a hot environment, therefore the purpose of this study was to investigate these factors using a Wattbike Pro. Twelve healthy, males completed three trials, of intermittent sprint protocols (ISP) of: 18 × 4-s maximal sprints in an environmental chamber (35.9 ± 0.7°C, RH 38.0 ± 1.9 %). Each 4-s sprint was followed by 116-s of active recovery. During each sprint, Power, Heart Rate (HR), thermal comfort and thermal sensation (-3/+3 scales), and RPE were assessed. Peak Average power (highest mean 4s sprint out of 18) 1435W, mean power 1028W, Coefficient of Variation (CV) 3.7 % meaningful change 37W. Peak power (highest instantaneous power of any 4s sprint) peak power 1556W, mean power 1151W, CV4.1 % meaningful change 46W. Average power output (mean average power of 18 sprints) peak power 1355W, mean power 938W, CV4.6 % equating to a meaningful change of 40W and also Average Peak (mean of highest instantaneous power of each 18 sprints) peak power 1454W, mean power 1052W, CV3.6 % 36W. This study confirms the reliability of the intermittent high intensity protocol in a hot environment.